2005
DOI: 10.1002/marc.200400452
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Functional Group on the Exfoliation of Clay in Poly(L‐lactide)

Abstract: Summary: A new method was attempted to improve the interaction between poly(L‐lactide) (PLLA) with a commercially available organoclay, Cloisite 25A (C25A), which was functionalized with (glycidoxypropyl)trimethoxysilane to introduce epoxy groups, and is referred to as twice‐functionalized organoclay (TFC). Tethering PLLA molecules to the epoxy groups on the surface of the TFC was attempted by melt compounding. X‐Ray diffraction and transmission electron microscopy images showed that fully exfoliated PLLA/TFC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 15 publications
(13 reference statements)
2
46
0
Order By: Relevance
“…34 The FTIR spectrum of C25AN in Figure 1 reveals that the peak at 3638 cm À1 of C25AN, corresponding to the stretching band of the terminal SiAOH on the silicate surface, was much less intense than that of pristine C25A; this confirmed the occurrence of a chemical reaction between the hydrolyzed silane monomers or oligomers with the silanol groups of C25A. Wei et al 35 and Chen and coworkers [31][32][33] observed similar results when they treated C25A with GPS. Figure 2 discloses the FTIR spectrum of C25AI.…”
Section: Silane Modificationsupporting
confidence: 70%
See 3 more Smart Citations
“…34 The FTIR spectrum of C25AN in Figure 1 reveals that the peak at 3638 cm À1 of C25AN, corresponding to the stretching band of the terminal SiAOH on the silicate surface, was much less intense than that of pristine C25A; this confirmed the occurrence of a chemical reaction between the hydrolyzed silane monomers or oligomers with the silanol groups of C25A. Wei et al 35 and Chen and coworkers [31][32][33] observed similar results when they treated C25A with GPS. Figure 2 discloses the FTIR spectrum of C25AI.…”
Section: Silane Modificationsupporting
confidence: 70%
“…Figure 3 presents XRD patterns of C25AE, C25AI, and C25AN, respectively. The modification with the silane compounds shifted the XRD peak of pristine C25A to a slightly lower angle, which indicated that the interlayer spacing of C25A was somewhat enlarged, that is, from d 001 ¼ [31][32][33] observed that d 001 of C25A was almost equivalent to that of C25AE. The different experimental results seem to originate from the fact that Chen and coworkers 31-33 modified C25A with GPS at room temperature, whereas the temperature used for the same purpose was 80 C in this study.…”
Section: Silane Modificationmentioning
confidence: 92%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13][14] However, there are only a few reports of preparing dual-functional clays by combining the two modification methods. [15][16][17][18][19] A twice-functionalized organoclay (TFC) was described involving reaction of a silane agent (glycidoxypropyl trimethoxysilane) with C25A, a montmorillonite modified with a quaternary ammonium salt. [15][16][17][18] Polymer nanocomposite compounded with this TFC showed improved elongation at break as well as increased tensile modules and tensile strength.…”
Section: Introductionmentioning
confidence: 99%